Differential maturation of chloride homeostasis in primary afferent neurons of the somatosensory system - Gilbert, Daniel; Franjic-Würtz, Christina; Lehmeyer-Funk, Katharina; Frings, Stephan; Möhrlen, Frank (International journal of developmental neuroscience, 2007)
Recent research into the generation of hyperalgesia has revealed that both the excitability of peripheral nociceptors and the transmission of their afferent signals in the spinal cord are subject to modulation by Cl− currents. The underlying Cl− homeostasis of nociceptive neurons, in particular its postnatal maturation, is, however, poorly understood. Here we measure the intracellular Cl− concentration, [Cl−]i, of somatosensory neurons in intact dorsal root ganglia of mice. Using two-photon fluorescence-lifetime imaging microscopy, we determined [Cl−]i in newborn and adult animals. We found that the somatosensory neurons undergo a transition of Cl− homeostasis during the first three postnatal weeks that leads to a decline of [Cl−]i in most neurons. Immunohistochemistry showed that a major fraction of neurons in the dorsal root ganglia express the cation-chloride co-transporters NKCC1 and KCC2, indicating that the molecular equipment for Cl− accumulation and extrusion is present. RT-PCR analysis showed that the transcription pattern of electroneutral Cl− co-transporters does not change during the maturation process.These findings demonstrate that dorsal root ganglion neurons undergo a developmental transition of chloride homeostasis during the first three postnatal weeks. This process parallels the developmental “chloride switch” in the central nervous system. However, while most CNS neurons achieve homogeneously low [Cl−]i levels - which is the basis of GABAergic and glycinergic inhibition - somatosensory neurons maintain a heterogeneous pattern of [Cl−]i values. This suggests that Cl− currents are excitatory in some somatosensory neurons, but inhibitory in others. Our results are consistent with the hypothesis that Cl− homeostasis in somatosensory neurons is regulated through posttranslational modification of cation-chloride co-transporters.